2021
DOI: 10.3390/cells10020352
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of PGC-1α-Dependent Transcriptional Programs in Neurological and Developmental Disorders: Therapeutic Challenges and Opportunities

Abstract: Substantial evidence indicates that mitochondrial impairment contributes to neuronal dysfunction and vulnerability in disease states, leading investigators to propose that the enhancement of mitochondrial function should be considered a strategy for neuroprotection. However, multiple attempts to improve mitochondrial function have failed to impact disease progression, suggesting that the biology underlying the normal regulation of mitochondrial pathways in neurons, and its dysfunction in disease, is more compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 328 publications
(402 reference statements)
1
34
0
Order By: Relevance
“…Early studies of PGC-1α identified its thermogenic role in skeletal muscle and brown fat, by uncoupling mitochondrial respiration in response to cold (Puigserver et al, 1998); interestingly, cold does not induce PGC-1α in the brain. There, its role may relate to protection against other stresses, including cytokines and lipopolysaccharides (McMeekin et al, 2021; Puigserver et al, 2001). For instance, PGC-1α leads to increases in expression of various enzymes involved in detoxification of reactive oxygen species (Austin and St-Pierre, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early studies of PGC-1α identified its thermogenic role in skeletal muscle and brown fat, by uncoupling mitochondrial respiration in response to cold (Puigserver et al, 1998); interestingly, cold does not induce PGC-1α in the brain. There, its role may relate to protection against other stresses, including cytokines and lipopolysaccharides (McMeekin et al, 2021; Puigserver et al, 2001). For instance, PGC-1α leads to increases in expression of various enzymes involved in detoxification of reactive oxygen species (Austin and St-Pierre, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in non-neuronal tissue have identified the transcriptional coactivator, PGC-1α (peroxisome proliferator activated receptor gamma coactivator 1α), as a key regulator of expression of nuclear encoded mitochondrial genes (Austin and St-Pierre, 2012; Handschin and Spiegelman, 2006; Lin et al, 2005; McMeekin et al, 2021). Its expression is induced by various triggers, including exercise, cold and fasting, and it then drives mitochondrial (Puigserver et al, 2001) and peroxisome biogenesis (Bagattin et al, 2010) and uncouples mitochondrial respiration (St-Pierre et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the early 2000s, PGC1α has attracted interest because of its important role in metabolic processes (including gluconeogenesis, glucose transport, and fatty acid oxidation), mitochondrial biogenesis, peroxisomal remodelling, and detoxification of reactive oxygen species (ROS) [2]. These effects are mediated through the regulation of a number of transcription factors, including nuclear respiratory factors (NFRs) NRF-1 and NRF-2 (interacting with Tfam, which drives transcription and replication of mtDNA), PPARs (PPARα, PPARδ/β, and PPARγ), thyroid hormone, glucocorticoid, oestrogen, and ERRs (oestrogen-related receptors) α and γ [3] (ERRα, ERRβ, and ERRγ), initiator element binding factor (YY1), myocyte-specific enhancer factors (MEF-2A, MEF-2C, MEF-2D), forkhead box O1 (FOXO1), and others [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is predominantly expressed in tissues with high energy demands such as heart, skeletal muscle, brown adipose tissue, liver, kidney and brain 1, 5 . Conversely, the expression level/ activity of PGC-1α and PGC-1α-dependent metabolic pathways are down-regulated in age and age-related diseases (muscle wasting, metabolic, neurodegenerative and neurodevelopmental disorders) 6, 7 , highlighting the key importance of this master homeostasis regulator in human physiology.…”
Section: Introductionmentioning
confidence: 99%